Improving the Dielectric Properties of High Density Polyethylene by Incorporating Clay-Nano Filler - Osama Elsayed Gouda; Sohair F. Mahmoud; Ahmed A. El-Gendy; Ahmed S. Haiba (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Polymer Nano composites have been used for various important industrial applications. The preparation of high density polyethylene composed with Na-montmorillonite Nano filler using melt compounding method for different concentrations of clay-Nano filler of 0%, 2%, 6%, 10%, and 15% has been successfully done. The morphology of the obtained samples was optimized and characterized by scanning electron microscope showing the formation of the polymer Nano composites. The thermal stability and dielectric properties were measured for the prepared samples. Thermal gravimetric analysis results show that thermal stability in polymer Nano composites is more than that in the base polymer. It has been shown that the polymer Nano composites exhibit some very different dielectric characteristics when compared to the base polymer. The dielectric breakdown strength is enhanced by the addition of clay-Nano filler. The dielectric constant and dissipation factor have been studied in the frequency range 200 Hz to 2 MHz at room temperature indicating that enhancements have been occurred in dielectric constant and dissipation factor by the addition of clay-Nano filler in the polymer material when compared with the pure material.